Association of Social Determinants of Health, Age, Sex and Sexual Exposure with HIV, Acquired Syphilis, and Mpox Detection Rates in Rio de Janeiro, Brazil: An Ecological Study - Lara E. Coelho; Rosa M. S. M. Domingues; Valéria Saraceni; Thiago S. Torres; Guilherme T. Goedert; Juliano Genari; Claudio J. Struchiner; Paula M. Luz (AIDS and Behavior, 2026)
Abstract This study employs a neighborhood-level Social Protection Index (SPI) to analyze how socioeconomic factors relate to the detection of HIV, acquired syphilis, and mpox. We conducted a retrospective analysis of 2022 surveillance data from Rio de Janeiro, Brazil, using case notifications geolocated to neighborhoods. Population data were obtained from the 2022 census. Neighborhoods were stratified by SPI into quintiles, and detection rates per 100,000 population were calculated by sexual exposure category. Associations between age, SPI, and detection rates were analyzed using multilevel Poisson regression models with random intercepts, fitted separately for men who gave sex with men (MSM), heterosexual men and women. Of 2,876 new HIV cases, the highest detection rate was among MSM (1,522/100,000). Of 13,676 syphilis cases, the male-to-female detection ratio was 1.7:1. Of 957 mpox cases, 80% occurred among MSM (812/100,000). HIV and syphilis clustered in lower SPI neighborhoods, while mpox concentrated in higher SPI neighborhoods. For HIV, younger age showed the strongest association among MSM, while lower SPI was strongest among women. For syphilis, younger age was most important among women, with strong SPI associations in both sexes. Among MSM, mpox was concentrated in 25-39 age group and higher SPI neighborhoods. Strong socioeconomic gradients among women reflect intersecting gender and socioeconomic inequalities. Among MSM, attenuated socioeconomic gradients and distinct mpox patterns suggest social and sexual networks shape transmission alongside structural factors. Prevention must address social determinants and network structures.